2018
DOI: 10.1021/acs.est.8b03121
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Transfer of 13C-Fullerenols from Scenedesmus obliquus to Daphnia magna in an Aquatic Environment

Abstract: Fullerenol, a water-soluble polyhydroxylated fullerene nanomaterial, enters aquatic organisms and ecosystems through different ingestion exposures and may pose environmental risks. The study of their uptake routes and transfer in aquatic systems is scarce. Herein, we quantitatively investigated the aquatic uptake and transfer of 13 C-fullerenols from Scenedesmus obliquus to Daphnia magna using 13 C-skeletonlabeling techniques. The bioaccumulation and depuration of fullerenol in Daphnia magna increased with exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…As a basis for aquatic food chains, algae are the source of food for various aquatic organisms and algae can promote the ingestion of NPs by organisms during feeding, thereby incorporating NPs into food chains (Figure 2) [23,30,92]. The transmission or enrichment of NPs through the aquatic food chain may lead to toxic effects on high trophic level organisms in the food chain.…”
Section: Fate Of Nps In the Aquatic Food Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…As a basis for aquatic food chains, algae are the source of food for various aquatic organisms and algae can promote the ingestion of NPs by organisms during feeding, thereby incorporating NPs into food chains (Figure 2) [23,30,92]. The transmission or enrichment of NPs through the aquatic food chain may lead to toxic effects on high trophic level organisms in the food chain.…”
Section: Fate Of Nps In the Aquatic Food Chainmentioning
confidence: 99%
“…The behavior of gold nanoparticles was studied in a model food chain consisting of a phytoplankton as food (Ankistrodesmus falcatus) and a zooplankton grazer (Daphnia magna), and a significant accumulation of Au NPs in the gut of Daphnia was observed [18]. Using stable isotope labeling techniques, it was revealed that carbon nanomaterials underwent complex aquatic accumulation and transfer from primary producers to secondary consumers (Scenedesmus obliquus-Daphnia magna food chain) [92]. Studies have shown that these NPs could accumulate in the digestive tract of Daphnia magna and exhibit chronic toxicity upon the growth and reproduction of Daphnia magna [32,95,96]; even the neonate production from adult daphnids was significantly reduced [97].…”
Section: Fate Of Nps In the Aquatic Food Chainmentioning
confidence: 99%
“…Finally, it is important to stress that hydroxylated fullerene (fullerenol or fullerol) is a water-soluble carbon nanomaterial that authors like Wang et al (2018) have shown that it is uptaken by green alga Scenedesmus obliquus and transferred to cladoceran Daphnia magna although with low efficiency.…”
Section: Environmental Concentrations and Behaviourmentioning
confidence: 99%
“…There have been many studies reported the negative effects of GRMs on different types of living organisms and a great possibility of bioaccumulation [9,10] . Studies using the body burden factor (BBF) to evaluate the accumulation of 14C-labeled graphene in E. coli, T. thermophila, D. magna, and D. rerio have showed that organisms exposed to graphene-containing culture medium have high potential of graphene accumulating [11] .…”
Section: Introductionmentioning
confidence: 99%